2022
DOI: 10.3390/cancers14225578
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Vascular Endothelial Growth Factor Receptor 1 (VEGFR-1) D16F7 Monoclonal Antibody Inhibits Melanoma Adhesion to Soluble VEGFR-1 and Tissue Invasion in Response to Placenta Growth Factor

Abstract: Placenta growth factor (PlGF) is a member of the vascular endothelial growth factor (VEGF) family involved in tumor-associated angiogenesis and melanoma invasion of the extra-cellular matrix (ECM) through activation of membrane VEGF receptor 1 (VEGFR-1). A soluble VEGFR-1 (sVEGFR-1) form is released in the ECM, where it sequesters proangiogenic factors and stimulates endothelial or tumor cell adhesion and chemotaxis through interaction with α5β1 integrin. The anti-VEGFR-1 monoclonal antibody (D16F7 mAb) inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The above circumstances occur in high levels of PlGF concentration in cancer tissues, which contribute to their proliferation, progression, local invasion, lymph, and distant metastases through blood flow, poor response to treatment, and implicate poor survival [14]. This occurs in various types of cancers, such as melanoma, small-cell lung cancer, thyroid carcinoma, serous ovarian cancer (OC), and oral squamous cell carcinoma [14,[19][20][21][22][23][24][25].…”
Section: Pigfmentioning
confidence: 99%
“…The above circumstances occur in high levels of PlGF concentration in cancer tissues, which contribute to their proliferation, progression, local invasion, lymph, and distant metastases through blood flow, poor response to treatment, and implicate poor survival [14]. This occurs in various types of cancers, such as melanoma, small-cell lung cancer, thyroid carcinoma, serous ovarian cancer (OC), and oral squamous cell carcinoma [14,[19][20][21][22][23][24][25].…”
Section: Pigfmentioning
confidence: 99%
“…Additionally, D16F7 mAb reduces PlGF production by melanoma cells. In conclusion, this study suggested that blocking PlGF/VEGFR-1 signaling with D16F7 mAb represents a promising strategy to counteract the metastatic potential of melanoma by inhibiting tumor-associated angiogenesis and invasion [35].…”
Section: Placental Growth Factor (Plgf)mentioning
confidence: 77%
“…VEGF-C and VEGF-D act as lymphangiogenic growth factors signaling via VEGFR-2 and VEGFR-3, and the lack of the VEGF-C in mice results in compromised development of the lymphatic vasculature [34,35]. VEGF-C is expressed in primary and metastatic melanoma and is associated with high intratumoral lymphatic density [36][37][38].…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…Numerous studies highlight the implication of microRNAs (miRNAs) in cancer research, as they play an important role in regulating cancer cells and impacting various aspects of cancer progression, including apoptosis induction, cell cycle regulation, metastasis promotion, and angiogenesis stimulation [30,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. In a recent investigation by Xiong et al [79], the effects of circSETD3, a circular RNA containing multiple miRNA binding sites, were studied in CCA cells.…”
Section: Potential Therapeutical Approachesmentioning
confidence: 99%